Education Quality Control Concepts and Applications - Musriadi (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
One of the problems faced by the government in the development of national education is the problem of quality. To improve the quality of education, it is necessary to improve the control function carried out by school principals and education supervisors. Control that will be able to provide significant benefits in improving quality if it is aimed at the input-process-output aspects of education. Control aimed at these components is called quality control. Quality control is an action that contains measurement or assessment and improvement activities. Controlling is a process that consists of planning (setting performance goals and standards), measuring actual performance, comparing performance and making improvements. Education quality control is aimed at aspects of the learning curriculum, student development and management aspects. These three target areas all refer to the optimal development of student competencies.